Inovasi Teknologi Dalam Pendidikan Klinis Keperawatan Sebagai Strategi Pembelajaran Kreatif: Apa Saja Manfaatnya Bagi Mahasiswa Keperawatan?: Sebuah Literatur Review - hutagaol, rutmauli (Jurnal Skala Kesehatan, 2023)
Nursing education consists of theory and practice. Half of all learning during the educational process is spent in a clinical practice learning environment. However, in practice there are still obstacles that cause the clinical practice process to not be optimal. The application of technological innovation really helps improve performance, performance and quality in all fields, including the world of education. Technology-based learning strategies in the field of education have been proven to increase students' knowledge and skills. This study aimed to identify the types and benefits obtained by students in the use of technological innovation in nursing student clinical practicum. The research method uses a Literature Review study of 10 articles using PRISMA from four online databases: ScienceDirect, ProQuest, Scopus, and Emerald Insight. The keywords used were "nursing education technology" OR "nursing academic technology". The results of this study was indicate that the application of technology-based learning strategies can improve students' abilities in clinical practice in aspects of knowledge such as knowledge related to treating seizures in children, treating foot ulcers obtained from 5 articles, aspects of skills such as skills for installing folley catheters obtained from 7 articles, and satisfaction student learning is obtained from 7 articles. Technology-based learning strategies in clinical practice provide benefits to students to increase their knowledge and skills. This needs to be considered by teaching lecturers to use technology-based learning strategies to enhance student learning experiences including and prepare them to face the real world as professional nurses.